2014
DOI: 10.14260/jemds/2014/3101
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Maternal Deaths in a Tertiary Care Centre

Abstract: BACKGROUND: Maternal death has been recognized as an area of maternal care that requires urgent attention.Making efforts to decrease maternal mortality is a matter of great concern to the obstetricians. MMR is a very sensitive index that reflects quality of reproductive care provided to the pregnant woman.OBJECTIVES: The aims of the study were to help generate information and knowledge regarding the causes and complications leading to maternal deaths (MDs) in an urban tertiary care hospital, to find if any of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
2
3
0
Order By: Relevance
“…Morsheda et al 3 reported 74% in the age group 20-35 years. 82.3% were from the rural area in our study, similar to the study by Vinayak et al 4 wherein they had 80.5%; Wahane et al 5 reported 77% from the rural set up. This high proportion of rural population may be due to delay in access to health care and lack of awareness and poor transport facilities.…”
Section: Discussionsupporting
confidence: 90%
“…Morsheda et al 3 reported 74% in the age group 20-35 years. 82.3% were from the rural area in our study, similar to the study by Vinayak et al 4 wherein they had 80.5%; Wahane et al 5 reported 77% from the rural set up. This high proportion of rural population may be due to delay in access to health care and lack of awareness and poor transport facilities.…”
Section: Discussionsupporting
confidence: 90%
“…This high proportion of ignorant rural population could be a reason for delayed access to health-care services. This was consistent to the studies performed by Vinayak et al 15 and Wahane and Koranna 16 who reported a rural domicile of 77%.…”
Section: Domicilesupporting
confidence: 92%
“…In a study conducted by Vinayak et al, only 11% patients travelled by ambulance. 11 Only 38% referrals travelled in ambulance while 62% patients used their private vehicles in Gwalior study. 6 58% travelled in ambulance provided by the referring hospital while 24% had to hire a private vehicle for inter-hospital transfer .Arranging a private vehicle when faced with obstetric emergency necessitating referral takes time and costs money.…”
Section: Mode Of Transportation To Referral Centrementioning
confidence: 89%
“…There were 82.3% were from the rural area, also in Vinayak et al and Wahane et al reported 77 %. [11][12] This high proportion of rural population may be due to delay in access to health care and lack of awareness and poor transport facilities. Infertility treated obstetric referrals were at significant risk of referral (p value=0.002).…”
Section: Domicilementioning
confidence: 99%